ABOUT THE GENERAL CONCEPT OF THE UNIVERSAL STORAGE SYSTEM AND PRACTICE-ORIENTED DATA PROCESSING - L. V. Rudikova (Системный анализ и прикладная информатика)
Approaches evolution and concept of data accumulation in warehouse and subsequent Data Mining use is perspective due to the fact that, Belarusian segment of the same IT-developments is organizing. The article describes the general concept for creation a system of storage and practice-oriented data analysis, based on the data warehousing technology. The main aspect in universal system design on storage layer and working with data is approach uses extended data warehouse, based on universal platform of stored data, which grants access to storage and subsequent data analysis different structure and subject domains have compound’s points (nodes) and extended functional with data structure choice option for data storage and subsequent intrasystem integration. Describe the universal system general architecture of storage and analysis practice-oriented data, structural elements. Main components of universal system for storage and processing practice-oriented data are: online data sources, ETL-process, data warehouse, subsystem of analysis, users. An important place in the system is analytical processing of data, information search, document’s storage and providing a software interface for accessing the functionality of the system from the outside. An universal system based on describing concept will allow collection information of different subject domains, get analytical summaries, do data processing and apply appropriate Data Mining methods and algorithms.